A damage index of indentation sensitivity in low velocity impact conditions. Issue 6 (11th April 2015) - Lopresto, V.; Caprino, G.; Leone, C.; Langella, A.
Abstract : The empirical model recently found by the authors for the prediction of the indentation depth was verified for composite laminates different in matrix and fiber subjected to low velocity impact loads. The data obtained in a previous research on common glass and carbon fiber laminates made by commonly used epoxy matrix, were here compared to the results obtained on laminates made by glass fibers immersed in phenolic matrix and novel basalt fibers immersed in epoxy resin. The model takes into explicitly account the tup diameter and presents the advantage that only a single material constant to be experimentally determined is necessary for the prediction. The comparison showed that the value of the constant is different for the different material systems analyzed so that it can be assumed as an index for the indentation sensitivity. POLYM. COMPOS., 36:987–991, 2015. © 2015 Society of Plastics Engineers